Chinese football violence: An extended theory of planned behavior model to predict fans’ violent behavioral intentions - Tian, Yuge; Ma, Chao; Shi, Zhenguo (Frontiers in Psychology, 2022)
This study introduced deindividuation variables and constructed a mechanism model of football fans' violent behavioral intentions in China based on Theory of Planned Behavior. Specifically, taking Chinese football fans as the research subjects, we used a structural equation model to explore the specific effects of subjective norms, perceived behavioral control, deindividuation, and attitude on violent behavior intentions. Our results showed that subjective norms (β= -0.132, P<0.01) had a significant negative predictive effect on football fans' violent behavioral intentions, while perceived behavioral control (β=0.297, P<0.01), deindividuation (β=0.239, P<0.01), and attitude (β=0.416, P<0.01) had a significant positive predictive effect. However, we found that attitude was the most important factor that predicted the football fans' violent behavioral intentions and played a mediating role between subjective norms and football fans' violent behavioral intentions, between perceived behavior control and football fans' violent behavioral intentions, and between deindividuation and football fans' violent behavioral intentions as well.